Meningkatkan komponen kebugaran jasmani atlet bola tangan melalui latihan Tabata pada saat terjadinya wabah COVID-19 - Setiawan, Edi; Iwandana, Dody Tri; Festiawan, Rifqi; Bapista, Ceu (Universitas Nusantara PGRI Kediri, 2020)
The purpose of this research was to improve the handball athletes’ physical fitness through Tabata training during the outbreak of COVID-19. This pre-experimental research used a One-Group Pretest-Posttest Design. The research participants were male handball athletes at amateur level (N = 30) (age = 21.8 ± 1.3 years, height = 169.6 ± 2 cm, weight = 60.7 ± 7 kg). All participants performed the Tabata training for 23 sessions with a frequency of 3 times a week. The athletes’ physical fitness level was measured using push-ups, curl-ups, V-sit and reach, as well as shoulder stretch. All research data were then analyzed using SPSS version 22 with a significance level of α 0.05. The results of this research found that the physical fitness components consisting of strength endurance (P<0.05), muscle strength (P>0.251), flexibility in the area of lower back and hamstrings (P<0.05) as well as upper arm flexibility (P<0.05) experienced differences before and after performing the Tabata training program. It is concluded that in response to the outbreak of COVID-19 throughout the world, Tabata is one alternative training to be performed by each handball athlete at home since Tabata training may provide various benefits in improving the handball atlethes’ physical fitness components.